Sirtuin 2 Deficiency Increases Bacterial Phagocytosis by Macrophages and Protects from Chronic Staphylococcal Infection - Ciarlo, Eleonora; Heinonen, Tytti; Théroude, Charlotte; Herderschee, Jacobus; Mombelli, Matteo; Lugrin, Jérôme; Pfefferlé, Marc; Tyrrell, Beatrice; Lensch, Sarah; Acha-Orbea, Hans; Le Roy, Didier; Auwerx, Johan; et al. (Frontiers in Immunology, 2017)
Sirtuin 2 (SIRT2) is one of the seven members of the family of NAD+-dependent histone deacetylases. Sirtuins target histones and non-histone proteins according to their subcellular localization, influencing various biological processes. SIRT2 resides mainly in the cytoplasm and regulates cytoskeleton dynamics, cell cycle and metabolic pathways. As such, SIRT2 has been implicated in the pathogenesis of neurodegenerative, metabolic, oncologic and chronic inflammatory disorders. This motivated the development of SIRT2-directed therapies for clinical purposes. However, the impact of SIRT2 on antimicrobial host defense is largely unknown. Here we address this question using SIRT2 knockout mice. We show that SIRT2 is the most highly expressed sirtuin in myeloid cells, especially macrophages. SIRT2 deficiency does not affect immune cell development and marginally impacts on intracellular signaling and cytokine production by splenocytes and macrophages.. However, SIRT2 deficiency enhances bacterial phagocytosis by macrophages. In line with these observations, in preclinical models, SIRT2 deficiency increases survival of mice with chronic staphylococcal infection, while having no effect on the course of toxic shock syndrome toxin-1, LPS or TNF induced shock, fulminant Escherichia coli peritonitis, sub-lethal Klebsiella pneumoniae pneumonia and chronic candidiasis. Altogether, these data support the safety profile of SIRT2 inhibitors under clinical development in terms of susceptibility to infections.